SISTEM INFORMASI PENJUALAN BATIK DIANA (SEBERANG KOTA JAMBI) BERBASIS WEBSITE - Wati, Nila; -, Riswan (JURNAL AKADEMIKA, 2024)
Abstract: During this time another obstacle experienced by batik sellers is intense competition, it makes the batik clothing industry processors must have a marketing strategy that is different from its competitors. Then the constraints that exist in Diana Batik, namely the batik sales system are still using manually, and there is still no information about Diana Batik. The system development method that I use in this study is the waterfall method that resolves the problem gradually and can check again if there are improvements at certain stages. Through this application, it is expected to facilitate the sales process and information about Diana Batik quickly and precisely.